Explaining traditions : folk behavior in modern culture - Bronner, Simon J. (University Press of Kentucky, 2011)
"Why do humans hold onto traditions? Many pundits predicted that modernization and the rise of a mass culture would displace traditions, especially in America, but cultural practices still bear out the importance of rituals and customs in the development of identity, heritage, and community. In Explaining Traditions: Folk Behavior in Modern Culture, Simon J. Bronner discusses the underlying reasons for the continuing significance of traditions, delving into their social and psychological roles in everyday life, from old-time crafts to folk creativity on the Internet. Challenging prevailing notions of tradition as a relic of the past, Explaining Traditions provides deep insight into the nuances and purposes of living traditions in relation to modernity. Bronner's work forces readers to examine their own traditions and imparts a better understanding of raging controversies over the sustainability of traditions in the modern world"--Provided by publisher.